Physicochemical characterization, molecular docking, and in vitro dissolution of glimepiride–captisol inclusion complexes - Pal, Arpita; Roy, Sudeep; Kumar, Akhil; Mahmood, Syed; Nasrin, Khodapanah; Thomas, Sabu; Agatemor, Christian; Ghosal, Kajal (American Chemical Society, 2020)
This present study investigated the effect of Captisol, a chemically modified cyclodextrin, on the in vitro dissolution of glimepiride. We prepared glimepiride–Captisol complexes of different mass ratios (1:1, 1:2, and 1:3 w/w) by a physical mixing or freeze-drying technique, and found that complexation with Captisol enhanced the water solubility of glimepiride. Molecular docking and dynamic simulation predicted complex formation; at the same time, Fourier transform infrared spectroscopy, differential scanning calorimetry, powder X-ray diffractometry, and scanning electron microscope indicated molecular interactions that support complexation. We also found that an inclusion complex was better than a physical mixture in enhancing the complexation of glimepiride with Captisol and enhancing water solubility. Phase solubility study of the glimepiride–Captisol complex showed an AL-type profile, implying the formation of a 1:1 inclusion complex. The study also revealed that pH influenced the stability of the complex because the stability constant of the glimepiride–Captisol complex was higher in distilled water of pH ∼6.0 than in phosphate buffer of pH 7.2.